2016
DOI: 10.1653/024.099.0307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Food Lures for Fruit Flies (Diptera: Tephritidae) Captured in a Citrus Orchard of the Serra Gaúcha

Abstract: The aim of the current study was to evaluate the effectiveness of 5 food lures for fruit fly monitoring in citrus orchards in the municipality of Pinto Bandeira, Rio Grande do Sul State, Brazil, from Nov 2012 to Oct 2013. Food lures included: 1) CeraTrap™ (undiluted), 2) Torula™ (6 tablets of 3 g/L), 3) BioAnastrepha (5%), 4) 10% corn syrup, and 5) 25% red grape juice (control). The lures were replaced weekly with the exception of CeraTrap™, which was replaced every 45 d. McPhail traps were baited with 300 mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…Of the 2,382 Tephritidae specimens collected in the current study, all insects belonged to the genus Anastrepha Schiner and were identified as Anastrepha fraterculus (Wiedmann, 1830), corroborating other studies carried out in Southern Brazil (Nava & Botton, 2010;Garcia & Norrbom, 2011;Nunes et al, 2012;Dias et al, 2013;Pereira-Rêgo et al, 2013;Bortoli et al, 2016).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Of the 2,382 Tephritidae specimens collected in the current study, all insects belonged to the genus Anastrepha Schiner and were identified as Anastrepha fraterculus (Wiedmann, 1830), corroborating other studies carried out in Southern Brazil (Nava & Botton, 2010;Garcia & Norrbom, 2011;Nunes et al, 2012;Dias et al, 2013;Pereira-Rêgo et al, 2013;Bortoli et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…In the neighboring properties, there were peach Prunus persica L. Batsch (Rosaceae) and grape Vitis spp. L. (Vitaceae) commercial orchards allowing the fruit fly occurrence and development (Garcia & Norrbom, 2011;Bortoli et al, 2016). In this case, the species would carry out migratory movements between the forest plants towards the vineyard.…”
Section: Resultsmentioning
confidence: 99%
“…In general, food lures used for the management of fruit flies are based on a combination of hydrolyzed protein (attractant) with sugar (phagostimulant), which stimulates the insects to search for and ingest the bait (Nestel et al, 2004;Bortoli et al, 2016). Baits that contained this mixture at the same concentration resulted in a higher mortality and lower LT 95 than with Success 0.02 CB which, in addition to the lethal agent spinosad, contains a mixture of sugar, protein, ammonium acetate, and other ingredients (Yee & Chapmamn, 2005), as well as hydrolyzed proteins of vegetable origin.…”
Section: Resultsmentioning
confidence: 99%
“…While the food bait used in Texas and Florida programs is a dry synthetic blend of food attractants (ammonium acetate and putrescine alone or in combination with trimethylamine), the food bait used in the California fruit fly detection system is an aqueous solution of hydrolyzed torula yeast-borax pellets (Burditt 1982;Scentry Biologicals Inc., Billings, Montana, USA). Recently, an alternative liquid bait derived from enyzymatic hydrolyzed animal protein, and known commercially as CeraTrap (Bioibérica, Barcelona, Spain), has been developed and found to be more attractive than the standard hydrolyzed yeast to the Mediterranean fruit fly (medfly), Ceratitis capitata (Wiedemann) (Shelly & Kurashima 2016) and various Anastrepha species (e.g., Lasa et al 2015;Bortoli et al 2016).…”
Section: Capture Of Melon Flies and Oriental Fruit Flies (Diptera: Tementioning
confidence: 99%